Exploring the translation–development interactions from an emergent semiotic perspective: A case study of the Greater Bay Area, China - Chen, Xi (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2022)
The Guangdong-Hong Kong-Macao Greater Bay Area (Greater Bay Area or GBA), a megalopolis in China, has developed rapidly and achieved remarkable results in recent years. This study aims to explore the translation–development interactions in the GBA from an emergent semiotic perspective. Following the studies on translation and development (Marais, 2014, 2018; Olivier de Sarden, 2005), this study views development as a semiotic process of making meaning under specific affordances and constraints, while translations could be regarded as meaningful intercultural mediations or adaptations that help to transcend language barriers and support regional development. Through exploring different translation practices in education, economics and the media, this study analyses how translation plays a mediating role in the development of the GBA in multiple respects. It first examines the adaptation of curriculum designs of translation courses in the universities of the GBA and then analyses the functions of the translation industry in support of the economic development of the GBA. Finally, it analyses the translations of international publicity material on the tourism websites of the GBA to explore the ways in which translation mediates in the cultural exchanges and coordinated developments regarding the GBA and its component parts. The research findings show that translation practices interact with the developmental contexts at the linguistic, economic and cultural levels, contributing to the coordinated development of the GBA.